Restoring Debt Sustainability After Crises : Implications for the Fiscal Mix - Baldacci, Emanuele (IMF Working Papers; Working Paper ;, 2010)
This paper analyzes the experience of 99 advanced and developing economies in restoring fiscal sustainability during 1980 - 2008 after banking crises, which led to large accumulation of public debt. It finds that successful debt reductions have relied chiefly on generation of large primary surpluses in post-crisis years through current expenditure cuts. These savings have been accompanied by growth-promoting measures and a supportive monetary policy stance. While these results are consistent with the existing literature, the paper finds that revenue-raising measures increased the likelihood of successful consolidation in countries that faced large adjustment needs after the crisis. This reflects the fall in effectiveness of spending cuts when deficit reduction needs are large independent of initial tax ratios.